Tinjauan Tentang Pengajuan Kasasi Penuntut Umum Atas Dasar Judex Factie Keliru Menafsirkan Kerugian Negara Dalam Perkara Korupsi - Sidabutar, Arinto Agustian (Sebelas Maret University, 2017)
This study aimed to describe and assess whether the submission of Cassation public prosecutor by reason Judex factie erroneous of interpreting state losses in a corruption case in accordance with the provisions of Article 253 Criminal Procedure Code. This research is a normative legal research which is prescriptive with the approach of the case (case approach) that is done in a way conduct a review of cases which deals with the issues faced and has been a court decision who already have legally enforceable. Technique analysis of legal materials being used is to use legal reasoning with the deduction method.The research instrument is the Supreme Court Decision No. 1022 K / Pid.Sus / 2014. This case shows the misinterpretation of state losses by Judex factie in the ruling Medan District Court No. 80 / Pid.Sus.K / 2013 / PNMdn, Where which are supposed to calculate the loss of state is BPKP be based Article 23E paragraph (1) The Constitution of the Republic of Indonesia of 1945, Government Regulation No. 60 of 2008 and the Constitutional Court Decision No. 31 / PUU-X / 2012.The results of research by the author shows that the submission of Cassation Prosecutor General with reason Judex factie erroneous of interpreting state losses in a corruption case conformable with the provisions of Article 253 paragraph (1) letter a Criminal Procedure Code. In this case Judex Factie had misapplied the law or had not apply the law as it should be with ignore the facts revealed at the hearing thus erroneous of interpreting state losses. This resulted in Judex facti in dropping its decision not meet humanity and justice. Keywords: Cassation, State Losses, The Criminal Procedure Code